2019
DOI: 10.1002/jnr.24500
|View full text |Cite
|
Sign up to set email alerts
|

Change in phospholipid species of retinal layer in traumatic optic neuropathy model

Abstract: Injured optic nerves induce death in almost all retinal ganglion cells (RGC) and cause a loss of axons. To date, we have studied injured RGC axon regeneration by using a traumatic optic nerve injury (TONI) rodent model, and we revealed that axonal regeneration is induced by the graft of an autologous peripheral nerve. The efficient approach to the regeneration of axons thus needs an environmental adjustment of RGC. However, the RGC environment induced by TONI remains unknown. Here, we analyzed female and male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Many RGCs are lost following ONC, resulting in blindness [ 63 ]. Reactive astrocyte accumulation may explain the underlying apoptotic processes in RGCs following TON [ 64 ]. Our results were similar to those of a previous study that revealed that astrocytes were activated, while their marker, GFAP, was substantially expressed on day 3 ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Many RGCs are lost following ONC, resulting in blindness [ 63 ]. Reactive astrocyte accumulation may explain the underlying apoptotic processes in RGCs following TON [ 64 ]. Our results were similar to those of a previous study that revealed that astrocytes were activated, while their marker, GFAP, was substantially expressed on day 3 ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Astrocytes have extensive proinflammatory capabilities and are regulators of inflammatory responses in the CNS [ 13 ]. Reactive astrocyte accumulation has been hypothesized to underlie RGCs apoptotic processes after TON [ 12 ]. In addition, studies have shown that excessive activation of astrocytes is detrimental to the repair of retinal ganglion cells after optic nerve injury [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Impairment of axonal regeneration and functional recovery results from damage to the central nervous system, enabling the transformation of naive astrocytes into reactive astrocytes and ultimately into scar-forming astrocytes [ 11 ]. Interestingly, a recent study found that the injured ON promotes astrocyte accumulation, glial scar formation, and RGCs death in the retinal layer [ 12 ]. In addition, astrocytes are emerging as central regulators of retinal ON inflammatory responses because they also have strong proinflammatory potential [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The impact of indirect trauma on the retina in this model has yet to be explored. Previous works on a different model of TON found that expression levels of phospholipid species were affected by traumatic optic neuropathy and may be associated with phospholipid species-specific functions [ 26 ]. Traumatic retinopathy brought on by either direct or indirect damage to the globe is referred to as commotio retinae.…”
Section: Discussionmentioning
confidence: 99%